Heterocene-catalyzed ethylene/oct-1-ene copolymerization under MAO-free and low-MAO conditions: The synthesis of highly statistical copolymers and their use in blending with HDPE. (17th April 2023) - Nifant'ev, Ilya E.; Vinogradov, Alexander A.; Vinogradov, Alexey A.; Minyaev, Mikhail E.; Bagrov, Vladimir V.; Salakhov, Ildar I.; Shaidullin, Nadim M.; Chalykh, Anatoly E.; Shapagin, Alexey V.; Ivchenko, Pavel V.
Abstract: Sandwich SiMe2 -bridged ansa -complexes of zirconium, containing heterocycle-fused η 5 -cyclopentadienyls, derivatives of 2, 5-dimethyl-7 H -cyclopenta[1, 2- b :4, 3- b ']dithiophene (2 ), 5, 10-dihydroindeno[1, 2- b ]indole (3 ) and 5, 6-dihydroindeno[2, 1- b ]indole (4 ) – 'heterocenes' – catalyzed ethylene homopolymerization and ethylene/oct-1-ene (E/O) copolymerization in the presence of triisobutylaluminum (TIBA) without MAO and perfluoroaryl borate activators, the benchmark bis(η 5 -fluorenyl) complex 1 was virtually inactive under these conditions. In the absence of MAO, E/O copolymerization resulted in a formation of copolymers not containing EOOE fragments even at E/O ratio of 2.4. Addition of 10 eq. of MMAO-12 resulted in increase of both catalytic activities of 2 –4 and oct-1-ene incorporation. E/O copolymers POE-05 (obtained on TIBA activated precatalyst 2 ) and POE-17 (obtained on TIBA/MMAO-12 activated precatalyst 4 ) were not inferior to the best commercial E/O copolymers in physico-mechanical characteristics at −45 °C. Extrusion blends of POE-05 and POE-17 with high density polyethylene (HDPE) demonstrated high impact strength and frost resistance. Graphical abstract: Image 1 Highlights: TIBA-activated heterocenes catalyze ethylene/oct-1-ene (E/O) copolymerization. Copolymers without EOOE fragments are formed up to E/O ratio of 2.4 Random E/O copolymers have promising low-temperature mechanical characteristics. Blends of E/O copolymers with HDPE have improved frost resistance.